Effectiveness of Using Hydrocolloid Dressing on the Incidence of Extravasation: an Experimental Study - Suriati, Rosi; Ramadhan, Rahmi; Atrisia, Anggun; Rahman, Waldi; Muharramah, Disa Hijratul (Indonesian Journal of Global Health Research, 2024)
Extravasation describes the process of leaking of substances injected into blood vessels into surrounding tissues. The incidence of extravasation ranges from 0.5%-6% in patients receiving peripheral chemotherapy. One way of treating extravasation is by using dressings. Hydrocolloid contains carboxymethyl cellulose (CMC) and gelatin. The function of hydrocolloid is to provide a moist environment, overcome inflammation, and protect epithelialised wounds from physical, chemical, and thermal trauma Objective: The purpose of the study was to determine the effectiveness of using Hydrocolloid dressing with regular wound care on the incidence of extravasation in the chronic room of dr. Mdjamil Hospital Padang Method: The type of research is quantitative with an Experimental Study design with a control Pre- Post Test. This study was conducted from February to July 2023 with 50 samples using the Simple Random Sampling technique. Data were collected using observation sheets, then tested with the General Linear Model Repeated Measure. Results: Based on the research results, a P value of 0.001 was obtained, giving hydrocolloid dressing had an effect in overcoming the incidence of extravasation after its use in children with cancer undergoing chemotherapy. The median score of extravasation on hydrocolloid was 7 and on ordinary wound care with a median score of 9 on the incidence of extravasation where the p-value was 0.018 Conclusions: There is an effect of using Hydrocolloid dressing on the incidence of extravasation in the chronic room of Dr. M. Djamil Hospital Padang. There is no effect of regular wound care on the incidence of extravasation in the chronic room of Dr. M. Djamil Hospital Padang.